2017
DOI: 10.1038/s41598-017-05140-3
|View full text |Cite
|
Sign up to set email alerts
|

Transglycosylation by a chitinase from Enterobacter cloacae subsp. cloacae generates longer chitin oligosaccharides

Abstract: Humans have exploited natural resources for a variety of applications. Chitin and its derivative chitin oligosaccharides (CHOS) have potential biomedical and agricultural applications. Availability of CHOS with the desired length has been a major limitation in the optimum use of such natural resources. Here, we report a single domain hyper-transglycosylating chitinase, which generates longer CHOS, from Enterobacter cloacae subsp. cloacae 13047 (EcChi1). EcChi1 was optimally active at pH 5.0 and 40 °C with a Km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 61 publications
(87 reference statements)
1
19
0
1
Order By: Relevance
“…The hydrolysis profile of Cm Chi1 is different from that of most chitinases from T. kodakaraensis KOD1 [ 42 ], Enterobacter cloacae subsp. cloacae [ 43 ] and P. barengoltzii [ 12 ]. For instance, Fu et al reported an exochitinase Pb Chi74 from P. barengoltzii possesses both exo activity and N -acetyl-β- d -glucosaminidase activity but no endo activity [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The hydrolysis profile of Cm Chi1 is different from that of most chitinases from T. kodakaraensis KOD1 [ 42 ], Enterobacter cloacae subsp. cloacae [ 43 ] and P. barengoltzii [ 12 ]. For instance, Fu et al reported an exochitinase Pb Chi74 from P. barengoltzii possesses both exo activity and N -acetyl-β- d -glucosaminidase activity but no endo activity [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis and transglycosylation (TG) are two significant processes that may determine the suitability of chitinases for specific roles. Chitinases interact with chitin either hydrolytically or by TG and some uniquely exhibit both properties [ 84 ]. Hydrolysis ( Figure 8 C) results in the generation of monomeric or dimeric glucosamine units with low degree of polymerization (DP) [ 24 ].…”
Section: Classification Based On Differences In Catalytic Mechanismsmentioning
confidence: 99%
“…Serratia proteamaculans ChiD ( Sp ChiD) was found to exhibit ‘transglyco-hydrolytic’ activity with a hyper-TG activity on DP2 to DP6 substrates, thus generating long chain COS of DP up to 13 and a hydrolytic property that breaks down DP8 and DP10 TG products to DP2 and DP4 COS respectively [ 24 ]. TG can however be of advantage if the chitinase has a hyper-TG activity like Enterobacter cloacae chitinase designated Ec Chi1, reported to produce long chain COS up to DP9 [ 84 ].…”
Section: Classification Based On Differences In Catalytic Mechanismsmentioning
confidence: 99%
“…They unravelled how a 13-residue protruding loop in the deep active binding cleft blocked a large number of subsites and suggested this structural characteristic to be responsible for the TG aptitude [67]. Furthermore, the majority of dual action mode chitinases seem to exhibit aromatic amino residues in their catalytic site, suggesting a processive mechanism [67,68]. The exact mechanism of TG events is not fully understood, however for the catalysis of disaccharides it could be shown that the TG is autocondensation-driven and has to happen faster than the glycosidic hydrolysis [69].…”
Section: Chitinases With Transglycosylation Capabilitiesmentioning
confidence: 99%
“…Consistent evidence from several studies illustrates how the transfer of COS is dependent on the amount and length of substrate and the proportion and nature of the enzyme. Hereby an excess amount of substrate appears to be beneficial for a TG activity, while a surplus of the glycosidase seems to push the reaction equilibrium towards a predominant hydrolysis agitation [66,68,70].…”
Section: Chitinases With Transglycosylation Capabilitiesmentioning
confidence: 99%